Assessing the effects of the neonicotinoid insecticide imidacloprid in the cholinergic synapses of the stellate cells of the mouse cochlear nucleus using whole-cell patch-clamp recording - Bal, Ramazan; Erdogan, Suat; Theophilidis, George; Baydas, Giyasettin; Naziroglu, Mustafa (Elsevier Science Bv, 2010)
Imidacloprid (IMI) is widely used systemic insecticide that acts as an agonist on nicotinic acetylcholine receptors (nAChRs). IMI has been reported to be more active against insect nAChRs (EC(50) 0.86-1 mu M) than it is against mammalian nAChRs (EC(50) 70 mu M). The objective of this study was to determine to what extent IMI affects the nAChRs of the stellate cells of mouse cochlear nucleus (CN), using whole-cell patch-clamp recording. Puff application of 1 mu M IMI had no significant effect on the membrane properties of the neurons tested, while a concentration of 10 mu M caused a significant depolarizing shift in the membrane potential and resulted in increases in the fluctuation of the membrane potential and in the frequency of miniature postsynaptic potentials (mpps) within less than a minute of exposure. IMI at concentrations >= 50 mu M caused a significant depolarizing shift in the membrane potential, accompanied by a marked increase in the frequency of action potential. IMI decreased the membrane input resistance and the membrane time constants. Bath application of 50 mu M d-tubocurarine (d-TC) reversibly blocked the depolarizing shift of the resting membrane potential and the spontaneous firing induced by IMI application in Current clamp and blocked the inward Currents through nicotinic receptors induced by IMI application in voltage clamp. Similarly, 100 nM alpha-bungarotoxin (alpha-BgTx) blocked the spontaneous firing induced by IMI (n = 3). The amplitude of the 100 mu M IMI-induced inward current at -60 mV holding potential was 115.0 +/- 16.2 pA (n = 7). IMI at a concentration of 10 mu M produced 11.3 +/- 3.4 pA inward current (n = 4). We conclude that exposure to IMI at concentrations >= 10 mu M for <1 min can change the membrane properties of neurons that have nAChRs and. as a consequence, their function. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Imidacloprid; Neonicotinoids; Toxicity; Nicotinic receptor; Patch clamp; Electrophysiology